2021
DOI: 10.3126/medphoenix.v6i1.33623
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Medical Students in Nepal: A Comparative Study

Abstract: Introduction: Medical education increases mental stress and affects the quality of life in medical students. Tough competition, academic performances, psychological distress, and unhealthy lifestyle add extra burden to the student. The study aimed to compare the quality of life among students of first and final year students. Materials and Methods: This was a cross-sectional study among first and final-year students of Bachelor in Medicine and Bachelor in Surgery (MBBS) degree at National Medical College… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The second most signi cant relationship to the (QoL) is found in correlation with the family income in the overall (QoL), general health, physical health, psychological health and environment; maximum scores for su cient income and minimum scores for insu cient income. Previous studies have shown that family/individual income is an important predictor of the (QoL) among medical students [14] [17] [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The second most signi cant relationship to the (QoL) is found in correlation with the family income in the overall (QoL), general health, physical health, psychological health and environment; maximum scores for su cient income and minimum scores for insu cient income. Previous studies have shown that family/individual income is an important predictor of the (QoL) among medical students [14] [17] [23] .…”
Section: Discussionmentioning
confidence: 99%